Isothermal oxidation property of plasma sprayed 20YSZ/NiAl thermal barrier coating - Phạm Thị, Lý; Nguyễn Văn, Tuấn; Nguyễn Tuấn, Anh; Phạm Thị, Hà; Đào Bích, Thủy; Lý Quốc, Cường; Võ An, Quân; Lê Hải, Đăng (Vietnam Journal of Science and Technology, 2025)
In this study, 20 wt.% yttria-stabilized zirconia (20YSZ) thermal barrier coatings (TBCs) were deposited by air plasma spraying (APS) on 310S stainless steel with NiAl as a bond coat. The TBCs were exposed to an isothermal oxidation test in an electric furnace under the air at 1000˚C for 8, 24, 48, 120, and 200 hours. Thermal oxidation characteristic of the coating was evaluated through cross-sectional structure, phase composition, and tensile adhesive strength. Results show that the 20YSZ coating consisted of mainly a thermodynamically stable cubic phase (Arkalite). The porosity, the thickness of the thermal growth oxide (TGO) layer, and the adhesive strength of the research sample had changes depending on the time of the isothermal oxidation. After exposure at 1000oC, the porosity of the coating could be reduced by up to 62.3% compared to the initial coating; the adhesion strength was improved significantly. The TGO thickness was high, but its growth rate tended to slow down and stabilize for the isothermal oxidation duration in a range of 24÷200 hours.